ISLAMIC PERSPECTIVE ON THE STREET LEVEL BUREAUCRATICS DILEMMA: DISCRETION VERSUS CORRUPTION IN PUBLIC SERVICE MANAGEMENT - Retnayu Prasetyanti; Dodi Faedlulloh (UIN Sunan Kalijaga, 2017)
Positions and authorities have become a commodity which always contested by humans. In fact, authority is an amanah to carry out the responsibility to serving the people. Nowadays, discretion has enhanced the role of Street Level Bureaucracy in the policy arena by authorizing a certain political power from the “top” to the “bottom”. By the emergence of governance era, discretionary power of street level bureaucracy was formerly designed as a means of public service innovation to transform red tape based public service delivery into social equity based public service management. Yet, in contrast to the objective of public service innovation, discretionary power is frequently misused by irresponsible actors in bureaucracy to legalize street level corruption which has triggered massive social distrust towards bureaucracy. Whereas Islam has clearly prohibited corruption as in Qur'an surah Al-Baqarah verse 188. By conducting literature study and theoretical analysis, this qualitative research highlights the urgency of discretion to uphold innovation in public service management with the spirit of sincerity and religiosity. As a conclusion, in the era of open government, socio-political control on discretion must be enhanced by establishing clear mechanism, high awareness, and good religiosity to guide the core role of street level bureaucrats as socio-professional worker.